2015 American College of Rheumatology Workforce Study: Supply and Demand Projections of Adult Rheumatology Workforce, 2015–2030. Issue 4 (29th March 2018) - Battafarano, Daniel F.; Ditmyer, Marcia; Bolster, Marcy B.; Fitzgerald, John D.; Deal, Chad; Bass, Ann R.; Molina, Rodolfo; Erickson, Alan R.; Hausmann, Jonathan S.; Klein‐Gitelman, Marisa; Imundo, Lisa F.; Smith, Benjamin J.; et al.
Abstract : Objective: To describe the character and composition of the 2015 US adult rheumatology workforce, evaluate workforce trends, and project supply and demand for clinical rheumatology care for 2015–2030. Methods: The 2015 Workforce Study of Rheumatology Specialists in the US used primary and secondary data sources to estimate the baseline adult rheumatology workforce and determine demographic and geographic factors relevant to workforce modeling. Supply and demand was projected through 2030, utilizing data‐driven estimations regarding the proportion and clinical full‐time equivalent (FTE) of academic versus nonacademic practitioners. Results: The 2015 adult workforce (physicians, nurse practitioners, and physician assistants) was estimated to be 6, 013 providers (5, 415 clinical FTE). At baseline, the estimated demand exceeded the supply of clinical FTE by 700 (12.9%). By 2030, the supply of rheumatology clinical providers is projected to fall to 4, 882 providers, or 4, 051 clinical FTE (a 25.2% decrease in supply from 2015 baseline levels). Demand in 2030 is projected to exceed supply by 4, 133 clinical FTE (102%). Conclusion: The adult rheumatology workforce projections reflect a major demographic and geographic shift that will significantly impact the supply of the future workforce by 2030. These shifts include baby‐boomer retirements, a millennial predominance, and an increase of female and part‐time providers, in parallel with an increased demand for adult rheumatology care due to the growing and aging US population. Regional and innovative strategies will be necessary to manage access to care and reduce barriers to care for rheumatology patients.